Effective group discussion : theory and practice - Galanes, Gloria J.; Adams, Katherine (Katherine L.) (N. York McGraw- Hill Education, 2019)
"Effective Group Discussion focuses on secondary groups, such as work groups, committees, task forces, self-directed work teams, and other small groups with tasks to complete. The text provides practical tips and also serves well as a reference source for advanced communication students, consultants, or group leaders"--
The small groups in everyone's life -- Human communication processes in the small group context -- The small group as a system -- Diversity and the effects of culture -- The members and their roles -- Communication and group culture: tensions, fantasy, socialization, norms, and climate -- Leading small groups: theoretical perspectives -- Leading small groups: practical tips -- Problem solving and decision making in groups: theoretical perspectives -- Problem solving and decision making in groups: practical tips and techniques -- Managing conflict in the small group -- Tools for assessing and evaluating groups.
Includes bibliographical references and indexes.
Keywords: Small groups; Communication in small groups; Group problem solving; Discussion